2019
DOI: 10.1002/cne.24818
|View full text |Cite
|
Sign up to set email alerts
|

Adult neurogenesis and gliogenesis in the dorsal and ventral canine hippocampus

Abstract: Dentate gyrus (DG) of the mammalian hippocampus gives rise to new neurons and astrocytes all through adulthood. Canine hippocampus presents many similarities in fetal development, anatomy, and physiology with human hippocampus, establishing canines as excellent animal models for the study of adult neurogenesis. In the present study, BrdU‐dated cells of the structurally and functionally dissociated dorsal (dDG) and ventral (vDG) adult canine DG were comparatively examined over a period of 30 days. Each part's n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 83 publications
(168 reference statements)
2
8
0
Order By: Relevance
“…Electrophysiological studies showed the rapid loss of immature neuronal properties, while immediate-early genes (Arc) expression profiles revealed an earlier neuronal activity of the septal neurons. Our marker expression studies support this notion by showing that newborn neurons of the septal DG showed an earlier expression of neuronal markers (DCX, NeuN) and an earlier acquisition of glutamate receptors (NMDA R1 and GluR2), in both the rat and canine DG (Bekiari et al, 2015a;Bekiari et al, 2020). Notably, there was a profound delay in the maturation time of adult-born neurons of the canine DG compared to the rat DG, which was anticipated by similar findings in other gyrencephalic species, such as the sheep and non-human primates.…”
Section: Neurogenesis Along the Septo-temporal Axis Of The Dg Of The Adult Mammalian Brainsupporting
confidence: 72%
See 2 more Smart Citations
“…Electrophysiological studies showed the rapid loss of immature neuronal properties, while immediate-early genes (Arc) expression profiles revealed an earlier neuronal activity of the septal neurons. Our marker expression studies support this notion by showing that newborn neurons of the septal DG showed an earlier expression of neuronal markers (DCX, NeuN) and an earlier acquisition of glutamate receptors (NMDA R1 and GluR2), in both the rat and canine DG (Bekiari et al, 2015a;Bekiari et al, 2020). Notably, there was a profound delay in the maturation time of adult-born neurons of the canine DG compared to the rat DG, which was anticipated by similar findings in other gyrencephalic species, such as the sheep and non-human primates.…”
Section: Neurogenesis Along the Septo-temporal Axis Of The Dg Of The Adult Mammalian Brainsupporting
confidence: 72%
“…However, when we performed a parallel stereological analysis of the newborn BrdU + cells and the total granule cell populations of the two dentate parts in the rat hippocampus we found an equal neurogenic potential of the septal and temporal part (Bekiari et al, 2015a). In the adult canine DG, however, similar stereological counting revealed an increased neurogenic potential of the septal DG part, which was attributed to the higher number of locally dividing radial glia-like NSCs (Bekiari et al, 2020). In both mammalian species studied, the developmentally 'older' temporal DG part showed an increased potential for viability of newborn neurons, achieving a balance between the birth rate of new-neurons and their accession into the local neuronal circuits.…”
Section: Neurogenesis Along the Septo-temporal Axis Of The Dg Of The Adult Mammalian Brainmentioning
confidence: 77%
See 1 more Smart Citation
“…Cells stained red for GFAP and green for NeuN were visualized and examined under a fluorescent microscope. Information for the antibody characterization was derived from the published work of Bekiari et al (2020) [ 25 ]. GFAP is an intracytoplasmic filamentous protein of astrocytes, proven to be a specific marker of cells of astrocyte origin, as the radial glia-like neural stem cells of the adult brain [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…Neurogenesis is a relatively new concept in neuroscience. The prevailing thought, based on canine and rodent adult models, is neurogenesis occurs in the dentate gyrus of the human adult hippocampus, and the subventricular (Spalding et al, 2013;Toda and Gage, 2018;Bekiari et al, 2020). NSC in these zones, can transition between quiescent and active states (Mohammad et al, 2019).…”
Section: Genetic Regulation Of Metabolic Switchmentioning
confidence: 99%